Analisis Potensi Retribusi Pasar Dan Kontribusinya Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Karanganyar - Susanti, Diyan Apriliya, Dra. Rina Trisnawati, Ak, M.Si., Ph.D (2017)
This research aims to know the potential acceptance of retribution of markets in the Region Boost Original Revenue (PAD) in the Karanganyar Regency. With the focus of the research that includes the type of facility and the magnitude of tariff levies, levy collection mechanism, targets and the realization of the acceptance of retribution in 2012, 2013, 2014, market levy contributions Karanganyar Regency in the original area of Revenue (PAD) as well as factors that barrier and supporters. Research methods used for writing this is descriptive research methods. Data collection techniques on this research by using the library (Library Research) and field research (Field Work Research) namely observation, interview (interview) directly with key informant. The informant and documentation. Data analysis the data used is an interactive model, namely data collection, reduction of data, exposure data and draw conclusions The results of this study indicate that retribution in Karanganyar market has increased significantly in increasing revenue, while its contribution over the past three years are at very less with a state indicator is always decreasing. The low contribution made by one of them due interpreter officers picked Karanganyar Market UPTD less than optimal in implementing the levy charged. During the implementation of fee collection has undergone a wide variety of supporting and inhibiting factors. Supporting factors in the fee collection is coordinating the implementation of all relevant agencies. Whereas the inhibiting factor is the lack of power because many officers were approaching full duty (retired).